2020
DOI: 10.1093/jcag/gwaa031
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Real-World Effectiveness of High- Versus Low-Volume Split Colonoscopy Preparations: An Experience Through the British Columbia Colon Cancer Screening Program

Abstract: Background The British Columbia Colon Screening Program (BCCSP) is a population-based colon cancer screening program. In December 2018, physicians in Vancouver, Canada agreed to switch from a low-volume split preparation to a high-volume polyethylene glycol preparation after a meta-analysis of studies suggested superiority of the higher volume preparation in achieving adequate bowel cleansing and improving adenoma detection rates. Aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Studies have shown that adequate patient instructions and lower volumes of bowel preparation increase patient compliance and willingness to repeat endoscopy 10,11 . However, reports on the effectiveness of ultra‐low volume bowel preparations pertaining to actual performance measures have suggested that they are not as effective as high‐ and low volume bowel preparations regimens 12–14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that adequate patient instructions and lower volumes of bowel preparation increase patient compliance and willingness to repeat endoscopy 10,11 . However, reports on the effectiveness of ultra‐low volume bowel preparations pertaining to actual performance measures have suggested that they are not as effective as high‐ and low volume bowel preparations regimens 12–14 …”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 However, reports on the effectiveness of ultra‐low volume bowel preparations pertaining to actual performance measures have suggested that they are not as effective as high‐ and low volume bowel preparations regimens. 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that compared with low-dose PEG, high-dose PEG has a higher success rate of bowel preparation and better bowel preparation conditions. [ 5 ] Investigators have also found that bowel preparation with 1L PEG is effective in patients with inflammatory bowel disease. [ 6 ] There are other reports suggesting that lower volumes of 1-L PEG might be associated with higher levels of bowel cleansing and higher BBPS scores in each segment compared with 2-L PEG.…”
Section: Introductionmentioning
confidence: 99%